2022
DOI: 10.3389/fpsyg.2022.1031615
|View full text |Cite
|
Sign up to set email alerts
|

What factors can support students' deep learning in the online environment: The mediating role of learning self-efficacy and positive academic emotions?

Abstract: IntroductionIn 2020, COVID-19 forced higher education institutions in many countries to turn to online distance learning. The trend of using online education has accelerated across the world. However, this change in the teaching mode has led to the decline of students' online learning quality and resulted in students being unable to do deep learning. Therefore, the current research, aimed at promoting deep learning in the online environment, constructed a theoretical model with learning self-efficacy and posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…This study shows that ICAs have a direct effect on AP, and EPs allow students to enjoy academic activity and have a greater perception of success. Some studies investigating PE, such as pride and hope, obtain results that confirm the increased perception of academic success [49,50]. According to Fredrickson [51], EPs enhance the acquisition of more personal resources for complex tasks that are present in teaching-learning processes [50].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This study shows that ICAs have a direct effect on AP, and EPs allow students to enjoy academic activity and have a greater perception of success. Some studies investigating PE, such as pride and hope, obtain results that confirm the increased perception of academic success [49,50]. According to Fredrickson [51], EPs enhance the acquisition of more personal resources for complex tasks that are present in teaching-learning processes [50].…”
Section: Discussionmentioning
confidence: 86%
“…Significantly, success through hard work, effort, and/or dedication (ICA) activates positive emotions in individuals, reinforcing self-efficacy and self-esteem [ 46 ] When students experience success through effort, they are able to increase their self-efficacy and self-esteem. Several studies have shown that success through effort is positively related to positive emotions, such as joy and satisfaction [ 47 , 48 , 49 ]. The present study supports these data by showing a positive correlation between internal controllable attributions to success and positive emotions and the mediating role of positive emotions between internal controllable attributions and academic achievement.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies provide preliminary empirical evidence for selfefficacy mediating between peer support and foreign language emotions in online contexts (Zhao and Liu, 2022;Derakhshan and Fathi, 2023). However, current research has limitations, including selfreport scales, a lack of differentiation between emotional, informational, and appraisal support types, and a focus on traditional classrooms rather than computer-mediated peer interactions.…”
Section: The Mediating Effect Of Self-efficacy On the Relationship Be...mentioning
confidence: 99%